2004
DOI: 10.1242/jeb.01151
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic deconstruction reveals involvement of manganese transportermalvolioin honey bee division of labor

Abstract: Molecular analysis of a complex behavioral phenotype is facilitated by dissecting it into simpler behavioral components. Using this approach, we present evidence implicating increased manganese transport by the malvolio (mvl) gene into brain cells as one factor that influences age-related division of labor in honey bee colonies. We studied mvl because manganese affects sucrose responsiveness in Drosophila melanogaster, and sucrose responsiveness is related to division of labor in honey bee colonies. Honey bee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 31 publications
8
115
0
Order By: Relevance
“…In our experiment, 1-day-old workers had weak expression levels of the Amobp5 and Acobp5 genes; this result is consistent with reports that the maturation of the olfactory neuron function begins 2 days before emergence (Masson and Arnold, 1984). When bees emerge, 1-week-old workers assume cleaning behaviors in their colony (Ben-Shahar et al, 2004;Leoncini et al, 2004;Whitfield et al, 2006). After about 1 week, bees begin to perform new roles, such as nursing, storing, and processing food (e.g., turning nectar into honey) (Trhlin and Rajchard, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In our experiment, 1-day-old workers had weak expression levels of the Amobp5 and Acobp5 genes; this result is consistent with reports that the maturation of the olfactory neuron function begins 2 days before emergence (Masson and Arnold, 1984). When bees emerge, 1-week-old workers assume cleaning behaviors in their colony (Ben-Shahar et al, 2004;Leoncini et al, 2004;Whitfield et al, 2006). After about 1 week, bees begin to perform new roles, such as nursing, storing, and processing food (e.g., turning nectar into honey) (Trhlin and Rajchard, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…This gene also mediates behavioral maturation in honey bees and, as its name implies, is elevated when individuals transition from nursing to foraging (Ben-Shahar et al, 2003). Similarly, increases in the gene malvolio (mvl), a manganese transporter initially described in Drosophila mutants with taste deficiencies (Rodrigues et al, 1995), and NPF are also associated with behavioral maturation to foraging in honey bees (Ben-Shahar et al, 2004). Interestingly, homologs of the NPY pathway also mediate transitions from solitary to social (grouping) behavior in Caenorhabditis elegans (De Bono and Bargmann, 1998) and Drosophila larvae (Wu et al, 2003), suggesting that the role of NPY/NPF in the mediation of social behaviors may be particularly ancient and well conserved across animals.…”
Section: Modification Of Feeding Circuits In the Evolution Of Eusociamentioning
confidence: 98%
“…Evidence also showed that this taste behavior holds true for honeybees, Apis mellifera. An increase in brain mvl expression leads to an elevation in Mn transport, sucrose responsiveness and, ultimately, division of labor within the colonies (Ben-Shahar et al, 2004).…”
Section: Possible Dmt1 Transport Of Mn In Other Systemsmentioning
confidence: 99%